Analisis bangkitan kendaraan terhadap dampak lalu lintas pada Ruas Jalan Metro Tanjung Bunga Kota Makassar - Abrar, Muhammad Rachmat; Said, Lambang Basri; Syafei, Ilham (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
In today’s modern era Currently, transportation is a basic need for all humans to be able to move from one place to another or from their origin to their desired destination. Traffic vehicle movement activities, and one of the infrastructure as a road section that has currently caused problems for the community in carrying out traffic movements, is on the Tanjung Bunga Metro Road section in Makassar City. The Tanjung Bunga Metro Road in Tamalate District, Makassar City, South Sulawesi is increasingly showing a condition that is quite serious, so that the public and the Makassar City Transportation Department are complaining about the difficulty of clearing up traffic jams on this section of the road. In accordance with the problem formulation, the research objectives are (1) Analyze the influence of vehicle generation on the impact of traffic jams on the Tanjung Bunga Metro road, Makassar city. (2) Factors that have a dominant influence on the impact of traffic congestion on the Tanjung Bunga Metro road, Makassar city. Research Method was carried out using a qualitative descriptive analysis method using SPSS Ver.21. The results obtained by the Regression equation model are as follows: Y = 1.807 - 0.208X1 + 0.245X2 + 0.039X3 + 0.244X4 + 0.558X5, with the following description: Variable X1 Aspect of Work Activities, with a coefficient value of 0.208. Variable X2 Aspect of Travel Destination, coefficient number 0.245, Variable or 59.70%.